ROTA BIOCEÂNICA E OS INDICADORES DE SAÚDE DO MUNICÍPIO DE PORTO MURTINHO-MS - KOWALSKI, Paloma Almeida; FERRI, Erika Kaneta; CUNHA, João Pedro Arantes da; CAVALCANTE, Emily Ruiz; MOTA, Natália Scigliano; LEMOS, Rachel Carvalho (ANAIS DO ENIC, 2022)
-